Changes in Pharyngeal Baseline Impedance in Patients With Laryngopharyngeal Reflux. (12th May 2020) - Doo, Jeon Gang; Kim, Su Il; Park, Jung Min; Kwon, Oh Eun; Lee, Young Chan; Eun, Young‐Gyu
Abstract : Objective: Few studies have investigated pharyngeal intraluminal baseline impedance (BI) levels in patients with laryngopharyngeal reflux (LPR). The aim of this study was to compare intraluminal BI levels between patients with LPR and healthy controls. Study Design: Retrospective case series. Setting: Tertiary care medical center. Subjects and Methods: We conducted a retrospective analysis of 24‐hour multichannel intraluminal impedance (MII)–pH monitoring results from patients with suspected LPR complaining of reflux symptoms. Patients with suspected LPR were divided into 2 groups according to the 24‐hour MII‐pH monitoring (LPR group: patients with symptoms with reflux events ≥1, symptom but no reflux [SNR] group: patients with symptoms but no reflux event). Healthy controls were recruited and also underwent 24‐hour MII‐pH monitoring. We compared the esophageal and pharyngeal BI levels and ratios between 3 groups. Results: Pharyngeal BI levels in the LPR group were significantly higher than in the healthy controls. In addition, the pharyngeal BI levels in the SNR group were significantly higher than in the healthy controls. All ratios of pharyngeal to distal esophageal BI levels in the LPR and SNR group were significantly higher than in the healthy controls. However, there were no significant differences in esophageal BI levels and ratios between the 3 groups. Conclusion: We found that the pharyngeal BI levels were higher in patients with LPR than in healthy controls. In addition, the pharyngeal BI levels measured by 24‐hour MII‐pH monitoring in patients with LPR symptoms, but without a reflux episode, were higher than in the healthy controls.